Effects of multimodal microstructure on fracture toughness and its anisotropy of LPSO-type extruded Mg-1Zn-2Y alloys - Soya Nishimoto; Taiga Yasuda; Koji Hagihara; Michiaki Yamasaki (Journal of Magnesium and Alloys, 2024)
The fracture toughness of extruded Mg-1Zn-2Y (at. %) alloys, featuring a multimodal microstructure containing fine dynamically recrystallized (DRXed) grains with random crystallographic orientation and coarse-worked grains with a strong fiber texture, was investigated. The DRXed grains comprised randomly oriented equiaxed α-Mg grains. In contrast, the worked grains included α-Mg and long-period stacking ordered (LPSO) phases that extended in the extrusion direction (ED). Both types displayed a strong texture, aligning the 〈101¯0〉 direction parallel to the ED. The volume fractions of the DRXed and worked grains were controlled by adjusting the extrusion temperature. In the longitudinal-transverse (L-T) orientation, where the loading direction was aligned parallel to the ED, there was a tendency for the conditional fracture toughness, KQ, tended to increase as the volume fraction of the worked grains increased. However, the KQ values in the T-L orientation, where the loading direction was perpendicular to the ED, decreased with an increase in the volume fraction of the worked grains. This suggests strong anisotropy in the fracture toughness of the specimen with a high volume fraction of the worked grains, relative to the test direction. The worked grains, which included the LPSO phase and were elongated perpendicular to the initial crack plane, suppressed the straight crack extension, causing crack deflection, and generating secondary cracks. Thus, these worked grains significantly contributed to the fracture toughness of the extruded Mg-1Zn-2Y alloys in the L-T orientation.